Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

The cultural politics of emotion - Ahmed, Sara (Edinburgh University Press, 2014)
This is a bold take on the crucial role of emotion in politics. Emotions work to define who we are as well as shape what we do and this is no more powerfully at play than in the world of politics. Ahmed considers how emotions keep us invested in relationships of power, and also shows how this use of emotion could be crucial to feminist and queer political movements. Debates on international terrorism, asylum and migration, as well as reconciliation and reparation are explored through topical case studies. In this textbook the difficult issues are confronted head on. New for this edition: a substantial 15,000-word Afterword on 'Emotions and Their Objects' which provides an original contribution to the burgeoning field of affect studies; a revised Bibliography; and updated throughout.
Keywords: approches et analyses; capitalisme; corps; discipline; féminisme; histoire et politique; militance; philosophie; queer; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; émotions; études culturelles

The promise of happiness - Ahmed, Sara (Duke University Press, 2010)
« The Promise of Happiness is a provocative cultural critique of the imperative to be happy. It asks what follows when we make our desires and even our own happiness conditional on the happiness of others: 'I just want you to be happy', 'I'm happy if you're happy'. Combining philosophy and feminist cultural studies, Sara Ahmed reveals the affective and moral work performed by the 'happiness duty', the expectation that we will be made happy by taking part in that which is deemed good, and that by being happy ourselves, we will make others happy. Ahmed maintains that happiness is a promise that directs us toward certain life choices and away from others. Happiness is promised to those willing to live their lives in the right way. Ahmed draws on the intellectual history of happiness, from classical accounts of ethics as the good life, through seventeenth-century writings on affect and the passions, eighteenth-century debates on virtue and education, and nineteenth-century utilitarianism. She engages with feminist, antiracist, and queer critics who have shown how happiness is used to justify social oppression, and how challenging oppression sometimes causes unhappiness. Reading novels and films including "Mrs. Dalloway", "The Well of Loneliness", "Bend It Like Beckham", and Children of Men, Ahmed considers the plight of the figures who are challenged by, and themselves challenge, the attribution of happiness to particular objects or social ideals: the feminist killjoy, the unhappy queer, the angry black woman, and the melancholic migrant. Through her readings, she raises critical questions about the moral order imposed by the injunction to be happy. »–Quatrième de couverture.
Keywords: approches et analyses; bonheur; care; discipline; inégalités; philosophie; queer; racisme; représentations; sciences humaines; sexisme; systèmes d'oppressions; thématiques; études culturelles

Les rabat-joie féministes (et autres sujets obstinés) - Ahmed, Sara (Cahiers du Genre, 2012)
Interrogeant la figure de la « féministe rabat-joie », cet article propose d’en explorer la négativité, aussi bien que la capacité d’agir dont elle est la promesse. Il s’agit ainsi, en repositionnant la pensée féministe comme critique de l’injonction au bonheur, de comprendre le sujet féministe en tant que sujet obstiné. L’obstination féministe est alors appréhendée comme le socle incertain d’une politique collective traduisant les émotions individuelles, la douleur ou la colère ressentie face aux injustices. Au-delà, la figure du sujet obstiné permet de saisir la façon dont, au sein des espaces féministes, les femmes noires ont pu être réduites à leur colère et désignées comme cause des divisions engendrées par le racisme. La position de sujet obstiné constituerait ainsi autant un lieu de tensions que de revendications politiques. https://www.saranahmed.com/
Keywords: 1900-1999; afro-féminisme; amériques; antiracisme; approches et analyses; care; cours; discipline; europe; fem1000; féminismes noirs; incontournable; intersectionnalité; luttes; militance; occident; orient; philosophie; phénoménologie; politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles